The role of inflammatory reaction in chronic venous disease of the lower limb - Vagholkar, Ketan; Garima, Shivangi; Kripalani, Yash (International Surgery Journal, 2019)
Chronic venous disease is the problem which is assuming alarming proportions in subjects whose occupation involves prolonged sitting or standing. The exact mechanism by which the venous system gets damaged continues to be a subject of endless research. The role of inflammation is a significant factor in the evolution of chronic venous disease. Awareness of this mechanism can help in both prevention and treatment of this complex vascular disorder. The paper reviews inflammatory mechanism underlying the pathogenesis of chronic venous disease in lower limbs.